No Islam but Islam - Moon, Farzana (Cambridge Scholars Publishing, 2015)
This book weaves its way into the fabric of Islam torn into shreds by the birth of many sects. The great twins, Shia and Sunni Islam; Ismaeli Islam; Ahmadiyya Islam; Wahhabi Islam; and Taliban Islam, to name a just few, dab the fabric of Islam in patches of color to define each sect, with the color of blood the largest patch. No Islam but Islam is written in response to a myriad of lies and distortions practiced by suicide bombers and extremists. It shows that the present state of violence, injustice and the oppression of women has nothing to do with Islam, but, rather, with man-made laws.